Multidimensional Approach To Conquer Piles with Homoeopathy & No Surgery (Homoeopathy for All, 2025)
Piles are another term for  haemorrhoids. Haemorrhoids are  collections of inflamed tissue in  the anal canal. They contain blood  vessels, support tissue, muscle, and  elastic fibers. Piles are certainly  one of the commonest ailments that  afflict mankind. This article provides  an overview of the aetiology,  diagnosis, and appropriate general  & homoeopathic management of  this disorder.
Keywords: support tissue; Pregnancy; Anal intercourse; slipping back immediately